Prescribing Trends in the Out Patient Department in a Tertiary Hospital in Bangladesh (Bangladesh Medical Journal, 2014)
A cross-sectional descriptive study was carried out among individuals attending the OPD of Medicine, Surgery and Gynaecology & Obstetrics from February 1st 2010 to April 30th 2010 in Sir Salimullah Medical College and Mitford Hospital, Dhaka, Bangladesh to see the patterns of prescriptions using World Health Organization core prescribing indicators and some additional indices. A total of 300 patients were included in this study. The average number of drugs per encounter was 3.6 and 1.33% drugs were prescribed by generic name. Use of antibiotic (48% of encounters) was frequent, but injection use (1.33% of encounters) was very low. Only 43.16% drugs were prescribed from EDL of Bangladesh. Percentage of encounters with an antiulcerant, a NSAID and a multivitamin & multimineral prescribed were 69%, 68.67% and 39.33% respectively. So the finding from current study shows a trend towards inappropriate prescribing, particularly the over-prescribing of antibiotics and under-prescribing of generic drugs & from essential drug list of Bangladesh. Hence, there is a need for effective intervention programme to encourage the physicians and healthcare providers in promoting more appropriate drug use. DOI: http://dx.doi.org/10.3329/bmj.v40i2.18496 Bangladesh Medical Journal 2011 Vol.40(2): 8-12